Leaders in the crucible : the moral voice of college presidents - Nelson, Stephen James, 1947- (Bergin & Garvey, 2000)
Annotation Is the college presidency merely a position in which one manages bureaucracies, garners wealth, and mediates ideological battles? On the contrary, the author argues that the moral leadership of college presidents is a tradition that the academy must sustain, and he details what can and ought to be expected of the office in the future.